Penggunaan Media Berbasis AutoPlay Media Studio 8 untukMeningkatkanAktivitas dan Hasil Belajar Siswa: Sebuah Inovasi Media Pembelajaran - Arsad Bahri1; Wahyu Hidayat2; Abdul Qalam Muntaha3 (Universitas Sebelas Maret, 2018)
The 21st century learning paradigm requires teachers to be able to use information and communication technology (ICT). One way to overcome the problem of low students' activities and learning outcome is the use of ICT-based learning media such as the use of AutoPlay Media Studio 8software as one of the learning innovations. The use of AutoPlay Media Studio 8-based learning media is one proof of teacher's ability in Technological, Pedagogical, Content Knowledge (TPCK). TPCK is a framework in designing new learning models by integrating technology in teaching. This research was a classroom action research conducted at Somba Opu Vocational School, which consists of two cycles. The subjects of the study were 21 students of class X1. Factors investigated were improvement of students’ activities and learning outcomes through the use of AutoPlay Media Studio 8-basedlearning media. The data of students’ learning activities were collected by using documentation and observation sheet, and the data of students’ learning outcomewere collected by using test of learning result at each end of cycle. The results showed that the use of AutoPlay Media Studio 8-based learningmedia can improve the activities and learning outcomes of students of class X1Somba Opu Vocational School. Therefore, teachers are required to have knowledge of pedagogy, content, and technology as teaching skill so as to create innovative learning